Application of irrigation management and water-lifting technologies to enhance fodder productivity in smallholder farming communities: a case study in Robit Bata, Ethiopia - Hussein, Misbah A.; Riga, F. T.; Derseh, M. B.; Assefa, T. T.; Worqlul, A. W.; Haileslassie, Amare; Adie, A.; Jones, Christopher S.; Tilahun, Seifu A. (MDPI, 2024)
Small-scale cultivation of irrigated fodder is emerging as a vital production system in mixed farming communities. Efficient water management plays a key role in enhancing forage production, especially in the face of changing climate. A field-scale experimental study was conducted in Robit Bata kebele, Ethiopia, with the following objectives: (1) to examine the effects of conventional farmers’ irrigation scheduling versus climate-based irrigation scheduling; and (2) to assess the influence of water-lifting technologies (manual pulley and solar Majipump) on dry matter yield (DMY), water productivity (WP), irrigation labor productivity (ILP), and water productivity in terms of crude protein and metabolizable energy (WP.CP and WP.ME) of Napier grass. The experiment used 10 farmers’ plots each with a size of 100 m2. Half of the plots were treated using farmers’ scheduling while the other half were treated using climate-based irrigation scheduling. Monitoring of irrigation water use and crop yield took place over two irrigation seasons from November 2020 to June 2021. Results showed there was an interaction effect of irrigation management (p = 0.019) and water-lifting technologies (p = 0.016) with season on DMY. The highest DMY occurred in the first irrigation season with climate-based scheduling and solar Majipump use. The interaction effect of irrigation management and season affected WP (p = 0.047). Climate-based scheduling had a higher WP in the first season, while farmers’ scheduling had a higher WP during the second season. On average, the solar Majipump outperformed the pulley, achieving 5 kg m−3 WP compared to the pulley’s 4 kg m−3 (p = 0.018). Emphasizing the seasonal impact, it is recommended to promote full irrigation (climate-based) in the first season for maximum yield and WP. Conversely, in the second season, advocating only deficit irrigation is advised due to water scarcity and sustainability concerns. Statistical parity in DMY and lower WP with full irrigation in the second season supports this recommendation, addressing the challenge of optimizing water use in the context of a changing climate and ensuring sustainable smallholder agriculture practices. Therefore, implementing appropriate irrigation management alongside efficient water-lifting technologies holds the potential to enhance fodder productivity and bolster smallholder farmers’ livelihoods. Future research should explore the comparative benefits of irrigated fodder versus other crops and the overall advantages of investing in irrigated fodder over vegetables.